The Problems, Difficulties and Guidelines to Develop the Zakat System in Contemporary Society a Case study: Narathiwat Province - สาและ, ตัรมีซี (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
This is quantitative research aiming to 1) Study the problems, difficulties and guidelines to develop the Zakat system in contemporary society a case study: Narathiwat Province and 2) study the comments and suggestions to develop the Zakat system in contemporary society a case study: Narathiwat Province by studying the Quran, Hadith, academic texts and other documents related to Zakat. The samples however were group of students, faculty members, academic scholars, community leaders, religious leaders (Imam), Muslim people and the Islamic Committee of Narathiwat in total of 400 people selected by simple random method. The instrument used as the reliability questionnaire is the Cronbach alpha coefficient of 0.99. While Data is analyzed by using the mean () and standard deviation (S.D.). The research found that 1) The problems and obstacles of developing the Zakat system in contemporary society is at a high level (= 3.69, S.D. = .97), while the study of the development of the Zakat system in contemporary society overall is at a high level (= 3.49, S.D. = 1.12) and 2) The comments and suggestions to develop the Zakat system in contemporary society is to establish an organization to manage the Zakat system or the Zakat fund in the province clearly to be accepted and a manifestation and management of the Zakat system that is valid in accordance with Islamic principles. This will benefit the community to improve the quality of life.